2008
DOI: 10.1002/cncr.23996
|View full text |Cite
|
Sign up to set email alerts
|

Critical and diverse involvement of Akt/mammalian target of rapamycin signaling in human lung carcinomas

Abstract: BACKGROUND: Aberrant signaling cascades emanating from epidermal growth factor receptor (EGFR) are involved in the complex network of oncogenic signaling in lung carcinomas. One representative cascade is the phosphatidylinositol 3‐kinase/Akt/mammalian target of rapamycin (mTOR) pathway. METHODS: The authors investigated the involvement of mTOR in the pathobiologic profiles of 150 specimens of lung carcinoma by immunohistochemistry and immunoblotting in correlation with the upstream and downstream proteins Akt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 41 publications
2
40
1
Order By: Relevance
“…Other studies have also investigated the p-AKT/p-mTOR pathway in BP-NETs, but their analysis of the percentage of immunoreactive tumor cells was combined with the staining intensity of the cells (26)(27)(28)(29). We decided to analyze our cases using only the percentage of positive cells, as our experience has indicated that the scoring system is highly subjective.…”
Section: Lesion Type P-akt Expression (No Of Patients) P-mtor Expresmentioning
confidence: 99%
“…Other studies have also investigated the p-AKT/p-mTOR pathway in BP-NETs, but their analysis of the percentage of immunoreactive tumor cells was combined with the staining intensity of the cells (26)(27)(28)(29). We decided to analyze our cases using only the percentage of positive cells, as our experience has indicated that the scoring system is highly subjective.…”
Section: Lesion Type P-akt Expression (No Of Patients) P-mtor Expresmentioning
confidence: 99%
“…The sensitivity and the specificity of these antibodies were earlier validated on a variety of cell lines and the tissue specimens by immunohistochemical and immunoblotting analysis. 7,22,23 Antibodies were visualized by a ChemMate Envision/ peroxidase complex kit (DAKO Japan, Kyoto, Japan). Immunohistochemical expression was evaluated by two of us (YD, SS) and the intensity of reactivity was evaluated as 'significant' or 'not-significant': 'significant' was defined as definite staining with higher intensity than that observed in non-neoplastic cells.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Furthermore, 'immunohistochemical expression level' was scored by three-tier system: negative (score 0), o10%; low (score 1), 10% or more, but o50%; high (score 2), 50% or more tumor cells with 'significant' staining. 7,23,24 When scores were classified into two groups for statistical analysis, 'low' and 'high' were combined as 'positive'.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations